Heritability of resting heart rate and association with mortality in middle-aged and elderly twins. Issue 1 (21st June 2017) - Jensen, Magnus T; Wod, Mette; Galatius, Søren; Hjelmborg, Jacob B; Jensen, Gorm B; Christensen, Kaare
Abstract : Objective: Resting heart rate (RHR) possibly has a hereditary component and is associated with longevity. We used the classical biometric twin study design to investigate the heritability of RHR in a population of middle-aged and elderly twins and, furthermore, studied the association between RHR and mortality. Methods: In total, 4282 twins without cardiovascular disease were included from the Danish Twin Registry, hereof 1233 twin pairs and 1816 'single twins' (twins with a non-participating co-twin); mean age 61.7 (SD 11.1) years; 1334 (31.2%) twins died during median 16.3 (IQR 13.8–16.5) years of follow-up assessed through Danish national registers. RHR was assessed by palpating radial pulse. Results: Within pair correlations for RHR adjusted for sex and age were 0.23 (95% CI 0.14 to 0.32) and 0.10 (0.03 to 0.17) for RHR in monozygotic (MZ) and dizygotic (DZ) twin pairs, respectively. Overall, heritability estimates were 0.23 (95% CI 0.15 to 0.30); 0.27 (0.15 to 0.38) for males and 0.17 (0.06 to 0.28) for females. In multivariable models adjusting for age, gender, body mass index, diabetes, hypertension, pulmonary function, smoking, physical activity and zygosity, RHR was significantly associated with mortality (eg, RHR >90 vs 61–70 beats per min: all-cause HR 1.56 (95% CI 1.21 to 2.03); cardiovascular 2.19 (1.30 to 3.67). Intrapair twin comparison revealed that the twin with the higher RHR was significantly more likely to die first and the probability increased with increase in intrapair difference in RHR. Conclusions: RHR is a trait with a genetic influence in middle-aged and elderly twins free of cardiovascular disease. RHR is independently associated with longevity even when familial factors are controlled for in a twin design.